Satisfaction Analysis of the Urban Landscape for 45-meter El-Goli Boulevard in Tabriz Using the SERVQUAL Model - saeedeh feizi; rasol darskhan; hasan sattarisarbangholi (تحقیقات کاربردی علوم جغرافیایی)
Both visual and service quality of urban landscape play an important role in the process of visual visibility assessment and effectiveness of these services as well. Given the fact that the existence of dead, cold, and soulless spaces in cities is affected by heterogeneity and visual contamination that is free from eye-catching and desirability. Therefore, this research seeks to evaluate the visual quality of the urban landscape of the Eil Goli district of Tabriz through the scale of the SERVQUAL tool. Understand the gap between the current situation and the expectations of Tabriz people on the 45-meter of El-Goli Boulevard towards the visual quality of the urban landscape; to realize the views and preferences of Tabriz citizens regarding the visual quality of urban landscape for the 45-meter El-Goli Boulevard in order to eliminate the weaknesses while improving its visual quality, taking into account the priorities and preferences of the people and to provide informative background for decision makers to improve the urban landscape design of Tabriz. So, data collection is carried out through the various sources in a comparative-analytical manner, using the documents, records and reports. The research statistical society includes citizens, specialists and experts and managers of the Department of Parks and Municipality of District 2 in this area which totally 310 questionnaires used for data collection. A questionnaire, expert analysis and library analysis will be carried out in the field observations for two sides of the El-Goli 45-meter Boulevard. The SPSS software, Klomgroph-Smirouph and One-way ANOVA used for analyses, checking the normal distribution of variables and comparing the five dimensions of service quality respectively. The results of the study indicate the relative satisfaction of the three groups under study. Also, some suggestions presented in order to increase urban satisfaction for the 45-meter boulevard of El-Goli, Tabriz city